Comparison of helical scan and standard rotation methods in single‐crystal X‐ray data collection strategies. (15th December 2016) - Polsinelli, Ivan; Savko, Martin; Rouanet-Mehouas, Cecile; Ciccone, Lidia; Nencetti, Susanna; Orlandini, Elisabetta; Stura, Enrico A.; Shepard, William
Abstract : Helical scans are compared with standard rotation methods in single‐crystal X‐ray diffraction experiments and, for certain cases, the helical scan methods improve the quality of the diffraction data and the electron density maps. Abstract : X‐ray radiation in macromolecular crystallography can chemically alter the biological material and deteriorate the integrity of the crystal lattice with concomitant loss of resolution. Typical alterations include decarboxylation of glutamic and aspartic residues, breaking of disulfide bonds and the reduction of metal centres. Helical scans add a small translation to the crystal in the rotation method, so that for every image the crystal is shifted to expose a fresh part. On beamline PROXIMA 2A at Synchrotron SOLEIL, this procedure has been tested with various parameters in an attempt to understand how to mitigate the effects of radiation damage. Here, the strategies used and the crystallographic metrics for various scenarios are reported. Among these, the loss of bromine from bromophenyl moieties appears to be a useful monitor of radiation damage as the carbon–bromine bond is very sensitive to X‐ray irradiation. Two cases are focused on where helical scans are shown to be superior in obtaining meaningful data compared with conventional methods. In one case the initial resolution of the crystal is extended over time, and in the second case the anomalous signal is preserved to provide greater effective multiplicity and easier phasing.